Controversies in the Management of Central Nervous System Coccidioidomycosis . (19th June 2022) - Thompson, George R; Ampel, Neil M; Blair, Janis E; Donovan, Fariba; Fierer, Joshua; Galgiani, John N; Heidari, Arash; Johnson, Royce; Shatsky, Stanley A; Uchiyama, Christopher M; Stevens, David A
Abstract: Central nervous system infection with Coccidioides spp. is fatal if untreated and complications occur even when therapy is directed by experienced clinicians. We convened a panel of clinicians experienced in the management of coccidioidal meningitis to summarize current controversies and provide consensus for the management of this difficult infection.